2007
DOI: 10.1111/j.1872-034x.2007.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography for patients with chronic hepatitis B and C virus infection: Non‐invasive, quantitative assessment of liver fibrosis

Abstract: These results suggest that FibroScan is an efficient and simple method for evaluating liver fibrosis in patients with chronic infection, both for HBV and HCV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 41 publications
2
82
0
1
Order By: Relevance
“…Several studies have reported that the inferior performance of LSM in patients with CHB compared to those with CHC could be explained by the histopathologic characteristics that HBV infection has a tendency to make heterogenous macronodular fibrotic structures in the liver [21,34,35]. In this study, most patients with cirrhosis (n=15) had a macronodular component to their fibrosis (seven patients with mixed micro-and macronodular cirrhosis and 8 patients with macronodular cirrhosis).…”
Section: Discussionmentioning
confidence: 60%
“…Several studies have reported that the inferior performance of LSM in patients with CHB compared to those with CHC could be explained by the histopathologic characteristics that HBV infection has a tendency to make heterogenous macronodular fibrotic structures in the liver [21,34,35]. In this study, most patients with cirrhosis (n=15) had a macronodular component to their fibrosis (seven patients with mixed micro-and macronodular cirrhosis and 8 patients with macronodular cirrhosis).…”
Section: Discussionmentioning
confidence: 60%
“…11 However, because IQR ⁄ M was investigated only in European patients with CHC, it cannot be applied directly to Asian patients with CHB because different BMI, the prevalence of metabolic syndrome and viral characteristics between CHC and CHB can influence LSM. [22][23][24] Therefore, investigation of factors that affect the diagnostic accuracy of LSM including IQR ⁄ M are needed in Asian patients with CHB. We followed the definition of 'significant discordance' by Lucidarme et al, considering the limitations of LB.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmed by several studies, FibroScan is an efficient and simple method for evaluating liver fibrosis in patients with chronic infection of both HBV and HCV. 77,78,84 Based on global evidence, it is recommended that Vietnam Ministry of Health develop and field test a standard diagnostic algorithm for advanced viral liver disease, combining a set of serological markers (eg, with a Hepascore type assay) and molecular assays (PCR viral load tests) to identify those who require HBV and HCV treatment and to monitor treatment effectiveness. Availability of the quality-assured elastography should also be expanded at referral hospitals.…”
Section: Current Response and The Suggested Way Forwardmentioning
confidence: 99%
“…[74][75][76][77][78][79][80][81][82][83] One of the most investigated scales is the Hepascore using a combination of commonly available laboratory markers. It reportedly has a general specificity of approximately 80% for identifying both significant and advanced fibrosis.…”
Section: Current Response and The Suggested Way Forwardmentioning
confidence: 99%